Structure and post-translational modification of the prostaglandin transporter - Peixuan Yu; Melanie A. Orlando; Benjamin J. Orlando (Communications Biology)
Abstract The prostaglandin transporter (PGT) is a member of the OATP family of membrane transporters. PGT mediates the uptake of prostaglandins from the extracellular environment to enable intracellular enzymatic degradation and termination of signaling. In addition to importing prostaglandins, PGT is also an essential core component of the Maxi-Cl channel, which facilitates cellular release of ATP and other small organic anions. Despite progress on understanding the (patho)physiological roles of PGT, and development of small molecules to inhibit this transporter, molecular details of the overall structure and transport mechanism remain elusive. Here we determined the cryo-EM structure of human PGT, which demonstrates an overall topology consistent with other OATPs despite possessing a dual transporter/channel functionality. We additionally investigated the role of eight potential disulfide bonds found in the extracellular loops of PGT and paralogous transporters. We demonstrate that six intra-loop disulfide bonds (C420-C511, C450-C470, C492-C474, C459-C507, C444-C494, C580-C594) are essential for proper N-glycosylation, plasma membrane trafficking, and prostaglandin import activity. In contrast, two inter-loop disulfides (C155-C587 and C143-C448) restricted maximal prostaglandin uptake, suggesting a possible regulatory role in modulating PGT activity. In total, our studies provide a fresh molecular perspective on the structure, post-translational modification, and overall function of PGT.